Impact of passive EDF location on the performance of L-band Brillouin-Erbium fiber laser - Al-Mashhadani T.F.; Al-Mansoori M.H.; Jamaludin M.Z.; Abdullah F.; Abass A.K.; Alit M.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Erbium; Fiber lasers; Fibers; Laser resonators; Location; Photonics; Single mode fibers; Brillouin pump; Brillouin Stokes; Brillouin-erbium fiber lasers; Cavity structure; Erbium doped fibers; Laser structures; Laser tunability; Multiwavelength; Pumping (laser)